2014
DOI: 10.2741/4277
|View full text |Cite
|
Sign up to set email alerts
|

CREG promotes vasculogenesis by activation of VEGF/PI3K/Akt pathway

Abstract: Knowledge about factors regulating vasculogenesis remains limited. The cellular repressor of E1A-stimulated gene (CREG) has been reported to be involved in maintaining cellular differentiation and endothelial homeostasis, thus we hypothesize that CREG may be a novel factor regulating vasculogenesis. By using mouse embryonic stem cells (ESC) derived embryoid body (EB) model, we confirmed expression of CREG was significantly up-regulated during EB differentiation. Overexpression of CREG in ESC led to accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Indeed, many of the TFs and chromatin modifiers identified amongst Etv6’s 540 direct target genes have previously been directly or indirectly implicated in the regulation of VegfA in endothelial and cancer cells. In addition to Foxo3 and Klf4 (the two targets examined in this study), these are Ets2, shown to down-regulate VegfA expression in HUVECs treated with arsenic trioxide (ATO) 39 , the tumour suppressor Rbl2 (also known as RB2/p130), that inhibits tumour formation in mice by inhibiting VegfA-mediated angiogenesis 37 , the transcriptional repressor Mecp2, that represses VegfA expression by binding to methylated CpG islands in the VegfA promoter 35 , and the transcriptional regulator Creg1, that regulates human endothelial homoeostasis in vivo and promotes vasculogenesis in mouse ES cells through the activation of VegfA 36 . These findings validate our experimental design and the robustness of the list of Etv6’s direct target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many of the TFs and chromatin modifiers identified amongst Etv6’s 540 direct target genes have previously been directly or indirectly implicated in the regulation of VegfA in endothelial and cancer cells. In addition to Foxo3 and Klf4 (the two targets examined in this study), these are Ets2, shown to down-regulate VegfA expression in HUVECs treated with arsenic trioxide (ATO) 39 , the tumour suppressor Rbl2 (also known as RB2/p130), that inhibits tumour formation in mice by inhibiting VegfA-mediated angiogenesis 37 , the transcriptional repressor Mecp2, that represses VegfA expression by binding to methylated CpG islands in the VegfA promoter 35 , and the transcriptional regulator Creg1, that regulates human endothelial homoeostasis in vivo and promotes vasculogenesis in mouse ES cells through the activation of VegfA 36 . These findings validate our experimental design and the robustness of the list of Etv6’s direct target genes.…”
Section: Discussionmentioning
confidence: 99%
“… 37 VEGF and angiogenin-1 are also important upstream molecules of PI3K/AKT signaling pathway. 38 , 39 Moreover, activation of the PI3K/AKT signaling pathway can also regulate the expression of VEGF and angiopoietin. 28 In this study, azelaic acid could not only regulate the expression of p-PI3K, p-AKT, p-mTOR, but also the expression of VEGF, COX-2, angiogenin-1 and HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the CD34 + population is undoubtedly the one that eventually differentiates to endothelial cells. Among the few proteins with increased abundance in CD34 − that might be involved in vasculogenesis were CREG1 74 LUM 75 and the LRP1 76 (Figure 4E, Supporting Table S-7). Interestingly, CREG1 and LUM are secreted, and LRP1 is cleaved 77 generating a soluble fragment.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In the CD34 – cells, we have identified five proteins with increased abundance (CD140B, PALLD, CREG1, LRP1, DAG1; Figure E) that are synthesized in vascular smooth muscle cells (VSMCs) or play a role in their differentiation and the proper investment of both large and small vessels with mural cells. ,, Importantly, hiPSCs-derived contractile and functional SMCs were CD34 – indicating that both types of progenitor stem cell (CD34 + and CD34 – ) have the machinery to differentiate SMCs/PCs. This is in agreement with the fact that during development, VSMCs arise from multiple independent origins or different subsets of mesoderm-committed cells …”
Section: Discussionmentioning
confidence: 99%